A marriage to scandalize the earl - Shepherd, Eva (Shepherd, Eva. Rakes, rebels and, rogues story., 2025)
"To save money, Lucy is to be married off before the Season even starts! So she arranges one clandestine night of fun-disguised as a maid-resulting in a thrilling kiss from a handsome gentleman... Sebastian Kingsley, Earl of Rothwell, believes his family is cursed by scandalous women. So he's arranged a respectable marriage with vicar's daughter Lucinda Everhart. Only, when she arrives at his estate, he gets a shudder of déjà vu. Lucinda is the vivacious "maid" from the gambling den-how can he marry her now?"--